Assessment of fish diversity and socio-economic condition of fishermen in Bangladesh - Jahan, Md Ishtiaque; Alam, Mohammad Shafiqul; Karim, Md Shamsul; Sultana, Nargis; Mamun, Md; Rafiquzzaman, SM (Asian Journal of Medical and Biological Research, 2018)
The main objectives of the study were to determine the present status of fish biodiversity and socio-economic condition of fishermen in Belai beel during February 2016 to September 2016 by survey method using questionnaires, field visit and interviewing with the fishermen. The results indicated that about 27 species of fish fauna were found in the Belai beel, among them 23 species were indigenous and 4 species were exotic. Major dominant species were Rui (Labeo rohita), Catla (Catla catla), Bata (Labeo bata), Shingi (Heteropeneustes fossilis), Magur (Clarius batrachus), Tengra (Mystus tengra), Chanda (Chanda nama), Kakila (Xenentodon cancila), Common carp (Cyprinus carpio), Mola (Amblypharyngodon mola) in the study area. During the study period two critically endangered (Puntius sarana, Pangasius pangasius), two endangered (Labeo bata, Channa marulius), and three vulnerable (Chanda nama, Channa orientalis, Notopterus notopterus) fish species were found in the Belai beel. Analysis of socio-economic condition of fishermen showed that maximum (70%) had nuclear family and others (30%) had joint family, as well as fishermen, belonged to the age groups of 31 to 40 years (50%) and the others were 15 to 30 (20%), 41 to 50 (18%), 51 to 60 (10%), 61 to70 (2%). Overall, the present study suggested that fishermen communities should be educated by creating awareness for the proper conservation, management, and enhancement of biodiversity in the Belaibeel. Asian J. Med. Biol. Res. March 2018, 4(1): 69-76